ON THE PROBLEMS OF THE MODEL OF PRIVATE PROSECUTION PROCEEDINGS EMBEDED IN THE NEW DRAFT OF THE CRIMINAL CODE OF THE REPUBLIC OF ARMENIA - Ghazaryan, Artak (State and Law, 2021)
In the article the author discusses the model of proceedings in case of private prosecution embedded in the Draft of the new Criminal Procedure Code of the Republic of Armenia. As a result of the study of some regulations of the Draft, the author raises some issues of Draft regulation problems and makes suggestions for their solution.